KERJA SAMA INDONESIA - DENMARK DI BIDANG ENERGI ANGIN DALAM KERANGKA KERJA SAMA ESP III DAN SSC PERIODE 2013-2020 - Zaki Mohammad Fadhlurrahman, (2022)
Indonesia has a high population growth and economic growth so that Indonesia is experiencing an increase in demand in the energy sector. Currently, Indonesia is still very dependent on the use of fossil energy. To reduce the long-term impact of using fossil energy and reduce dependence on fossil energy, Indonesia is establishing a bilateral cooperation with Denmark to promote the energy transition in the wind energy sector. This study aims to explain the implementation of cooperation between Denmark and Indonesia in the field of wind energy. This study uses a qualitative method with data sources obtained from official reports, books, journal articles, and direct interviews with parties related to the research conducted. The main concept used in this research is international cooperation according to Robert Keohane where to achieve a common goal requires action from the actors. Cooperation within the existing framework of cooperation as well as through close bilateral partnerships will support the framework of cooperation for the parties concerned. The Danish experience can provide extraordinary insights and experiences to help Indonesia make the most of wind energy.